Discovery of Potent Disheveled/Dvl Inhibitors Using Virtual Screening Optimized With NMR-Based Docking Performance Index - Hori, Kiminori; Ajioka, Kasumi; Goda, Natsuko; Shindo, Asako; Takagishi, Maki; Tenno, Takeshi; Hiroaki, Hidekazu (Frontiers in Pharmacology, 2018)
Most solid tumors have their own cancer stem cells (CSCs), which are resistant to standard chemo-therapies. Recent reports have described that Wnt pathway plays a key role in self-renewal and tumorigenesis of CSCs. Regarding the Wnt/β-catenin pathway, Dvl (mammalian Dishevelled) is an attractive target of drug discovery. After analyzing the PDZ domain of human Dvl1 (Dvl1-PDZ) using NMR, we subjected it to preliminary NMR titration studies with 17 potential PDZ-binding molecules including CalBioChem-322338, a commercially available Dvl PDZ domain inhibitor. Next, we performed virtual screening using the program GOLD with nine parameter sets. Results were evaluated using the NMR-derived docking performance index (NMR-DPI). One parameter set of GOLD docking showing the best NMR-DPI was selected and used for the second virtual screening against 5,553 compounds. The second docking trial identified more than 1,700 compounds that exhibited higher scores than CalBioChem-322338. Subsequent NMR titration experiments with five new candidate molecules (NPL-4001, 4004, 4011, 4012, and 4013), Dvl1-PDZ revealed larger chemical shift changes than those of CalBioChem-322338. Finally, these compounds showed partial proliferation inhibition activity against BT-20, a triple negative breast cancer (TNBC) cell. These compounds are promising Wnt pathway inhibitors that are potentially useful for anti-TNBC therapy.